Risk Factors for Contrast-Induced Nephropathy in Patients Undergoing Elective Coronary Angiography in Taiwan: A Multicenter Analysis - John Hwang; Michelle Kim (Phlox Institute: Indonesian Medical Research Organization, 2023)
Introduction: Contrast-induced nephropathy (CIN) is a serious complication following coronary angiography (CAG) that can lead to increased morbidity, mortality, and healthcare costs. Identifying risk factors for CIN is crucial for risk stratification and implementing preventive strategies. This multicenter study aimed to investigate the independent predictors of CIN in Taiwanese patients undergoing elective CAG. Methods: This retrospective cohort study included patients who underwent elective CAG at three tertiary medical centers in Taiwan between January 2019 and December 2023. CIN was defined as an increase in serum creatinine ≥0.5 mg/dL or ≥25% from baseline within 48-72 hours post-procedure. Demographic, clinical, and procedural data were collected. Multivariable logistic regression analysis was performed to identify independent predictors of CIN. Results: A total of 3,850 patients were included in the study. The overall incidence of CIN was 7.8% (n=300). Independent predictors of CIN included age (OR 1.03, 95% CI 1.02-1.05, p<0.001), diabetes mellitus (OR 1.87, 95% CI 1.35-2.58, p<0.001), chronic kidney disease (OR 3.65, 95% CI 2.58-5.16, p<0.001), anemia (OR 1.62, 95% CI 1.12-2.34, p=0.01), contrast volume (OR 1.01, 95% CI 1.00-1.02, p=0.02), and left ventricular ejection fraction (LVEF) <40% (OR 1.75, 95% CI 1.21-2.53, p=0.003). Conclusion: Age, diabetes mellitus, chronic kidney disease, anemia, contrast volume, and reduced LVEF were independent predictors of CIN in Taiwanese patients undergoing elective CAG. These findings highlight the importance of careful patient selection and risk mitigation strategies to minimize the occurrence of CIN in this population.